2009
DOI: 10.1007/s00535-009-0092-0
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical circumferential distribution of esophagogastric junctional lesions: anatomical and physiological considerations

Abstract: Several components of the gastrointestinal tract including the esophagogastric junction (EGJ) show circumferential asymmetry in the formation of pathological lesions, which is caused by the morphological and functional asymmetry of the gastrointestinal tract. Pressure in the lower esophageal sphincter (LES) is higher on the left posterior side as compared to the right anterior side, which may partly explain why Mallory-Weiss tears frequently occur on the right side wall of the EGJ. Lower LES pressure in the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 25 publications
3
21
1
1
Order By: Relevance
“…An interesting observation in this study is that the esophageal cardiac glands were found to be primarily located on the left-posterior side of the esophageal wall, which is opposite the main site of mucosal injury in patients with LAclassification A and B grade reflux esophagitis (25,26). The circumferential localization of mucosal injury in cases of A and B grade reflux esophagitis was shown to largely fit the direction of prolonged acid exposure in a study that used a recently developed 8-channel device with radially arrayed pH sensors (27).…”
Section: Discussionmentioning
confidence: 79%
“…An interesting observation in this study is that the esophageal cardiac glands were found to be primarily located on the left-posterior side of the esophageal wall, which is opposite the main site of mucosal injury in patients with LAclassification A and B grade reflux esophagitis (25,26). The circumferential localization of mucosal injury in cases of A and B grade reflux esophagitis was shown to largely fit the direction of prolonged acid exposure in a study that used a recently developed 8-channel device with radially arrayed pH sensors (27).…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, SIM was frequently found in the 0-3 o'clock area, which was a similar location to where EAC was most preferentially found [6-9]. The presence of SIM can be limited by sampling error in mucosal biopsies and shows a patchy distribution in the BE mucosa; however, one of the goals of the “Seattle” protocol is to detect dysplasia or SIM [10].…”
Section: Discussionmentioning
confidence: 99%
“…Also, we did not analyze the association between the localization of SIM, molecular alterations or mAb Das-1 reactivity, and acid reflux to the esophagus using a circumferential pH sensor array catheter [6]. It has been reported that acid reflux in BE patients predominantly occurs in the right anterior side (0-3 o'clock quadrant) of the distal esophagus [6]. Additionally, four-quadrant biopsies were not obtained from the patients with EAC prior to endoscopic resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophagogastric junctional lesions, including reflux esophagitis, ruptured esophageal varices, Mallory-Weiss tears, BE, and BE-associated neoplasia, have been frequently recognized to have a unique asymmetrical circumferential distribution, likely due to their anatomical and physiological properties [25]. To date, several reports have demonstrated the circumferential distribution of BE-associated neoplasia.…”
Section: Circumferential Localization Of Be-associated Neoplasiamentioning
confidence: 99%